Rapid biochemical methane potential prediction of urban organic waste with near-infrared reflectance spectroscopy. (1st August 2017) - Fitamo, T.; Triolo, J.M.; Boldrin, A.; Scheutz, C.
Abstract: The anaerobic digestibility of various biomass feedstocks in biogas plants is determined with biochemical methane potential (BMP) assays. However, experimental BMP analysis is time-consuming, costly and challenging to optimise stock management and feeding to achieve improved biogas production. The aim of the present study is to develop a fast and reliable model based on near-infrared reflectance spectroscopy (NIRS) for the BMP prediction of urban organic waste (UOW). The model comprised 87 UOW samples. Additionally, 88 plant biomass samples were included, to develop a combined model predicting BMP. The coefficient of determination ( R 2 ) and root mean square error in prediction (RMSEP ) of the UOW model were 0.88 and 44 mL CH4 /g VS, while the combined model was 0.89 and 50 mL CH4 /g VS. Improved model performance was obtained for the two individual models compared to the combined version. The BMP prediction with NIRS was satisfactory and moderately successful. Highlights: Developing a use of NIRS for BMP prediction of urban organic waste. R 2 and RMSEP of the urban organic waste model was 0.88 and 44 mL CH4 /g VS. Slightly larger model error for the combined BMP data for variety of samples. The BMP prediction with NIRS was satisfactory and moderately successful.